2006
DOI: 10.1007/s00216-006-0656-2
|View full text |Cite
|
Sign up to set email alerts
|

l-Glutamate biosensor for estimation of the taste of tomato specimens

Abstract: An amperometric biosensor has been developed for measurement of Umami, or the taste based on the amount of L-glutamate, in tomato foods. The biosensor is based on an enzyme-mediator system in which L-glutamate oxidase is used for biochemical oxidation of L-glutamate and a tetrafulvalene-tetracyanoquinodimethane (TTF-TCNQ) paste, prepared from the mixture of TTF-TCNQ salt, graphite powder, and silicone oil, serves as the mediator. The limit of detection, calculated by use of a four-parameter logistic model, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 42 publications
2
26
0
4
Order By: Relevance
“…Downregulation of both FUL1 and FUL2 impairs color development in the fruit and affects the expression of many genes involved in ripening processes, such as cell wall modification, cuticle formation, and aroma production. Interestingly, our data also revealed that Glu accumulates to a lesser extent in the fruits silenced for FUL1 and FUL2 than in the wild type, suggesting a role for FUL1/2 in the production of this major taste component of cultivated tomato fruits (Pauliukaite et al, 2006;Sorrequieta et al, 2010).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Downregulation of both FUL1 and FUL2 impairs color development in the fruit and affects the expression of many genes involved in ripening processes, such as cell wall modification, cuticle formation, and aroma production. Interestingly, our data also revealed that Glu accumulates to a lesser extent in the fruits silenced for FUL1 and FUL2 than in the wild type, suggesting a role for FUL1/2 in the production of this major taste component of cultivated tomato fruits (Pauliukaite et al, 2006;Sorrequieta et al, 2010).…”
Section: Discussionsupporting
confidence: 49%
“…The total free amino acid content of tomato fruits increases approximately fivefold during ripening, which contributes markedly to the taste of the fruit. However, Glu seems particularly important for a tasty tomato, since all cultivated varieties have much higher contents than wild tomatoes (Boggio et al, 2000;Pauliukaite et al, 2006). Glu was also found to be responsible for the characteristic umami taste of tomatoes and other foods like cheese and mushrooms (Bellisle, 1999).…”
Section: Ful1/2 Regulate Glu Accumulation During Ripeningmentioning
confidence: 99%
“…In this case TTF-TCNQ is interesting since the results for electrochemistry of GOx at the single crystal electrodes are inconsistent with a simple homogeneous mediation mechanism or with simple heterogeneous redox catalysis [23]. Such a phenomenon was observed because TTF-TCNQ acts not as electron transferor and as redox mediator at the same time and two different processes compete at the same time causing inconstancies mentioned above, as was observed with glutamate oxidase [52].…”
mentioning
confidence: 80%
“…The TTF-TCNQ -electron transfer complex -along with application to glucose determination is also used to develop biosensors for other substrates, in particular hydrogen peroxide [43], lactate [39,63], fructose [64], glutamate [52], lactulose [65], biological purines [28], dopamine [37], hypoxanthine [40,42,49], acetylcholine and choline [32,66], methanol [53,67], sulfite [41], and formaldehyde [34] ( Table 1). These biosensors operate in the potential range from À 0.075 V to þ 0.30 V vs. SCE, and the potential values usually are limited by the electrochemical decomposition of the mediator complex.…”
Section: Biosensorsmentioning
confidence: 99%
“…4) may be a result of different kinetics or reaction mechanism occurring under different concentration regimes. Nevertheless, a four-parameter logistic model [39] was used to evaluate the response for calibration purposes. This flexible calibration model can be expressed by the equation [40]:…”
Section: Biosensor Calibrationmentioning
confidence: 99%